Social norms and goal-setting interventions to promote responsible gambling in low-to-moderate online gamblers: protocol for a four-arm randomised controlled feasibility study. Issue 3 (14th March 2023) - Arden-Close, Emily; Thomas, Sarah; Bush-Evans, Reece; Wang, Ruijie; Bolat, Elvira; Hodge, Sarah; Phalp, Keith; McAlaney, John
Abstract : Introduction: Gambling is increasingly recognised as an important public health issue. Problem gambling is associated with highly negative impacts on physical, psychological and social well-being, not only for those who gamble but also for those around them. There has been a rapid expansion of internet gambling and attributes such as continuous play and instant rewards, and enhanced privacy may lead to a greater likelihood of gambling-related harms. In this randomised controlled feasibility study, we are testing (1) the acceptability and feasibility of three online responsible gambling interventions targeting people with low-to-moderate risk of online problem gambling and (2) the feasibility of a future full-scale randomised controlled trial (RCT) to test their effectiveness and cost-effectiveness. Methods and analysis: Four-arm randomised controlled feasibility study with qualitative substudy. One-hundred and forty UK residents with low-to-moderate risk of online gambling recruited via gambling operators and social media will be randomised (1:1:1:1) to either (1) goal setting, (2) descriptive norms messages (challenge perceptions of peer behaviours), (3) injunctive norms messages (challenge perceptions of peer attitudes) and (4) control (delayed intervention). Interventions will be delivered over 6 weeks and individually tailored. Outcomes, administered online, will be measured at baseline, 7 weeks, and 3 and 6 months post randomisation (including gambling risk behaviours and cognitions, anxiety and depression, quality of life, health use and productivity). Analyses will be descriptive, focusing on feasibility and acceptability of the interventions and study procedures. Telephone/online interviews, with a subsample of approximately 30 participants, will elicit experiences of participating in the study. Prespecified progression criteria will guide decisions around whether to progress to a definitive RCT. Ethics and dissemination: Ethical approval obtained from Bournemouth University Research Ethics Committee (reference number 33247). Participants will be given a participant information sheet plus a 'Key Facts' summary and will provide informed online consent. Findings will be published in peer-reviewed journals and presented at conferences and public engagement events. Trial registration number: ISRCTN37874344 .